Three-Week Treadmill Exercise Enhances Persistent Inward Currents, Facilitates Dendritic Plasticity, and Upregulates the Excitability of Dorsal Raphe Serotonin Neurons in ePet-EYFP Mice - Ge, Renkai; Dai, Yue (Frontiers in Cellular Neuroscience, 2020)
Exercise plays a key role in preventing or treating mental or motor disorders caused by dysfunction of the serotonergic system. However, the electrophysiological and ionic channel mechanisms underlying these effects remain unclear. In this study, we investigated the effects of 3-week treadmill exercise on the electrophysiological and channel properties of dorsal raphe nucleus (DRN) 5-HT neurons in ePet-EYFP mice, using whole-cell patch clamp recording. Treadmill exercise was induced in ePet-EYFP mice of P21-24 for three weeks and whole-cell patch clamp recording was performed on EYFP positive 5-HT neurons from DRN slices of P42-45 mice. Experiment data showed that 5-HT neurons in the DRN were heterogeneous population with multiple firing patterns (single firing, phasic firing, and tonic firing). Persistent inward currents (PICs) with multiple patterns were expressed in 5-HT neurons and composed of Cav1.3 (Ca-PIC) and sodium (Na-PIC) components. Exercise hyperpolarized voltage threshold for action potential (AP) by 3.1±1.0 mV (control: n=14, exercise: n=18, p=0.005) and increased AP amplitude by 6.7±3.0 mV (p=0.031) and firing frequency by more than 22% especially within a range of current stimulation stronger than 70 pA. Three-week treadmill exercise was sufficient to hyperpolarize PIC onset by 2.6±1.3 mV (control: -53.4±4.7 mV, n=28; exercise: -56.0± 4.7 mV, n=25, p=0.050) and increase PIC amplitude by 28% (control: 193.6±81.8 pA; exercise: 248.5±105.4 pA, p=0.038). Furthermore, exercise hyperpolarized Na-PIC onset by 3.8±1.8 mV (control: n=8, exercise: n=9, p=0.049) and increased Ca-PIC amplitude by 23% (p=0.013). The exercise-induced enhancement of PIC amplitude was mainly mediated by Ca-PIC and hyperpolarization of PIC onset by Na-PIC. Moreover, exercise facilitated dendritic plasticity which was shown as increased number of branch points by 1.5±0.5 (p=0.009) and dendritic branches by 2.1±0.6 (n=20, p=0.001) and length by 732.0±100.1 μm (p<0.001) especially within the range of 50-200 μm from the soma. Functional analysis suggested that treadmill exercise enhanced Na-PIC for facilitation of spike initiation and Ca-PIC for regulation of repetitive firing. We concluded that PICs broadly existed in DRN 5-HT neurons and could influence serotonergic neurotransmission in juvenile mice and that three-week treadmill exercise induced synaptic adaptions, enhanced PICs and thus upregulated the excitability of the 5-HT neurons.